Public administration and growth of corruption in government contracting (2016)
The problem of corruption in public administration is a very important factor growing for years, the ineffectiveness of the developing country are likely to be more corrupt, the need for some public official and nonconformity with the entities where they work, they can be factors that influence to incur such crimes. At international level Colombia is among the most corrupt and least efficient countries in Latin America, it is clear that our country has long tried to promote and perform checks, although very poor, which brings in up possible solutions to these problems increasingly they impoverish a country, and try to sensitize the public treasury is a whole country.